The write off - McDowell, Kara (Berkley Romance, 2026)
"It's been thirteen years since Mars Darling first met West Emerson on a bench outside their writing class. What started out as a friendly rivalry turned into a best friendship and then, for a time that felt all too brief, a romance. Now over a decade later, as Mars stands at their college campus as a once-esteemed YA fantasy author, ready to take on a book festival, she comes face to face with West. The muse behind her infamous trilogy's heartthrob hero, the man who betrayed her in the worst way. Mars is determined not to let her comeback tour be ruined by the fact that West is also at the festival as an author. But the longer they are on the campus that holds so many shared memories, the more time they have to untangle their past, and Mars starts to question if maybe it's not only her writing career that deserves a second chance. Told in two unfolding timelines-Mars and West's frenzied college days where they grapple with their undeniable connection, and their tension-filled present of heartache and familiar yearning-this charming romance shows that while you can't rewrite the past, it's never too late to chase your happily ever after and get back the one that got away"--